Penegakan Hukum Tindak Pidana Penyalahgunaan Niaga Liquefied Petroleum Gas (Lpg) di Bangka Belitung Dalam Tahapan Penyidikan - Riatati, Ade; Agustian, Rio Armanda; Toni, Toni (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
The crime of misuse of Liquefied Petroleum Gas (LPG) is a serious problem in Indonesia, including in Bangka Belitung, which harms the state and society. This research aims to analyse law enforcement in the investigation of the crime and identify the factors that influence it. The research method used is empirical juridical with a case approach. The results show that law enforcement in the investigation stage has run well through systematic procedures, including arrest, search, seizure, and detention. Preventive efforts are also made through coordination with related parties. Supporting factors include the professionalism of investigators, coordination of related agencies, community support, and clear regulations, while the main inhibiting factor is the constraints on the storage of LPG evidence.